Pengaruh Komunikasi, Disiplin dan Motivasi Kerja terhadap Kinerja Karyawan PT Graha Auto Plus Batam - Mediana Mediana; M. Khoiri (Ekonomis: Journal of Economics and Business, 2023)
In today's era, every company has an important part in carrying out its vision and mission, namely Human Resources (HR). So that the goal is achieved, every company must move its employees so that employee performance will progress and the company will continue to grow. This study aims to examine how far the influencing factors are from Communication, Discipline, and Work Motivation on Employee Performance at PT Graha Auto Plus Batam. The sample used was 106 respondents from employees of PT Graha Auto Plus Batam. The results showed that communication has a positive significant effect on employee performance, t count has a value of 4.033 and the significant value of the communication variable is 0.001. Work Discipline Has a positive significance on employee performance, the t count is 4.589 and the significant value of the discipline variable is 0.001. While Work Motivation has a positive and significant effect on employee performance, the t count is 2.400 and a significant value of 0.018 so which means that communication has a positive and significant influence, Discipline has a positive and significant influence and Work Motivation has a positive and significant influence and simultaneously communication, discipline and work motivation significant on the performance of employees of PT Graha Auto Plus Batam.